Cognitive Function in People With Pediatric Multiple Sclerosis Over 2 Years - O'Neill, Kimberly A; Charvet, Leigh; Waltz, Michael; George, Allan; Benson, Leslie A; Gorman, Mark P; Mar, Soe S; Ness, Jayne M; Schreiner, Teri; Waubant, Emmanuelle; Weinstock-Guttman, Bianca; Wheeler, Yolanda S; et al. (Neurology, 2025)
Pediatric multiple sclerosis (MS) affects children and adolescents at an important time for neurologic and cognitive development. Although cognitive impairment has been described, few longitudinal studies of cognitive functioning in pediatric MS with matched controls are available. Here, we report the 2-year follow-up cognitive results of a cohort of participants with MS and healthy controls (HCs) recruited from multiple regions of the United States. Three cohorts-participants with pediatric MS, age-matched pediatric HC, and adults with early-onset MS-were recruited across 7 sites through the United States Network of Pediatric MS Centers. Two cognitive batteries, Cogstate Brief Battery (CBB) and Brief International Cognition Assessment for MS (BICAMS), were administered at baseline and follow-up. The primary outcome was the change in CBB composite z-score compared between groups. Change in BICAMS composite z-score was also compared, as were change in z-scores of individual measures. Reliable change indices (RCIs) were calculated to determine meaningful change over time. A total of 63/72 (87.5%) of participants with pediatric MS, 81/99 (81.8%) of pediatric controls, and 48/66 (72.7%) of adults with MS returned for follow-up a mean 2.15 ± 0.27 years later. Participants with pediatric MS were median 17.4 years [IQR 16.0-18.3] at time of follow-up with median disease duration of 3.9 years [IQR 2.8-5.6]. 71% were female. There were no significant differences in change in CBB composite z-scores among pediatric MS and pediatric HC groups (0.10 vs 0.31, = 0.113) or between the pediatric and adult MS groups (0.10 vs 0.00, = 0.987). Although on RCI of the CBB, 80% of participants with pediatric MS were either stable or improved, more of the pediatric MS group declined relative to the control group 19.7% vs 5.1%, = 0.022. Most individuals with pediatric MS early in their disease showed stable cognitive function over a 2-year period and had longitudinal changes that were largely similar to pediatric controls. A subset of participants with pediatric MS declined in cognitive processing speed relative to pediatric controls.